Expanding the Presence of Primary Services at Rapid Response Team Activations: A Quality Improvement Project. Issue 1 (January 2018) - Gallo de Moraes, Alice; O'Horo, John C.; Sevilla-Berrios, Ronaldo A.; Iacovella, Gina; Lenhertz, Andrea; Schmidt, Julie; Elmer, Jennifer; Oeckler, Richard; Caples, Sean; Jensen, Jeffrey B.
Abstract : Rapid response teams (RRTs) were implemented to provide critical care services for deteriorating patients outside of intensive care units. To date, research on RRT has been conflicting, with some studies showing significant mortality benefit and reduction in cardiac arrest events and others showing no benefit. However, studies have consistently showed improved outcomes when RRTs work closely with primary services. Baseline data analysis at our institution found that primary services were present only on 50% of RRT activations. This quality improvement project aimed to improve the presence of primary services during RRT activations by 25%. With a survey, the main barrier that prevented primary services to be present was identified as the primary services' failure to recognize them as a crucial part of the RRT. Education tools and in-person sessions were implemented reinforcing the importance of primary services presence during RRT activations. The intervention leads to increasing presence of primary services at RRT activations, transfers to higher level of care, and changes in code status. However, there was no difference in hospital or intensive care unit length of stay or in survival.